2014
DOI: 10.1007/s00436-014-3851-7
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal IFN-γ production is associated with protection from clinical signs, but not with elimination of worms, in Echinostoma caproni infected-mice

Abstract: In the present paper, we assess the relationship between the expression of IFN-γ and the development of clinical signs in Echinostoma caproni-infected mice. For this purpose, we studied the course of the infection in three mouse strains: ICR (CD-1®) (a host of high compatibility with E. caproni), BALB/c (a prototypical Th2 strain), and BALB/c deficient for IFN-γ mice (IFN-γ(-/-)). Infection in ICR mice is characterized by the elevated expression of IFN-γ and iNOS in the intestine concomitantly with the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…Our results indicate that partial and complete resistance to E. caproni infections are associated with goblet cell hyperplasia and changes in mucus glycosylation at the time of challenge infection. Although previous studies have suggested that goblet cell hyperplasia has little effect on resistance to E. caproni infections 16 45 46 , our current results are somewhat confusing. Primary infection induced a goblet cell hyperplasia of about 4-fold greater than in negative controls from 4 wppi.…”
Section: Discussioncontrasting
confidence: 66%
“…Our results indicate that partial and complete resistance to E. caproni infections are associated with goblet cell hyperplasia and changes in mucus glycosylation at the time of challenge infection. Although previous studies have suggested that goblet cell hyperplasia has little effect on resistance to E. caproni infections 16 45 46 , our current results are somewhat confusing. Primary infection induced a goblet cell hyperplasia of about 4-fold greater than in negative controls from 4 wppi.…”
Section: Discussioncontrasting
confidence: 66%
“…This cytokine plays an important role in macrophage activation and modulation of the adaptive T helper one (Th1) immune response (Hu & Ivashkiv, 2009). On the other hand, IFN-γ cannot stimulate a T helper two (Th2) response, which would be the most effective modulation towards elimination of the parasite (Cortes et al ., 2014). It is important to mention that the levels of INF detected were lower than the last point of the standard quantification curve for this cytokine (fig.…”
Section: Discussionmentioning
confidence: 99%
“…E. caproni infection induces strong local Th1-type responses in ICR mice, which are characterized by high levels of IFN-γ [ 14 ]. In this context, Cortés et al [ 28 ] showed that local IFN-γ production in this host strain seems to play a dichotomous role, inhibiting protective Th2 responses and inducing inflammation and, concomitantly, reducing the severity of the disease and protecting ICR mice from infection-induced morbidity and mortality. INF-γ −/− mice, however, exhibit an enhanced intestinal pathology and lethality after E. caproni infection.…”
Section: Discussionmentioning
confidence: 99%